Transformable multirotor with two-dimensional multilinks: Modeling, control, and whole-body aerial manipulation. (August 2018) - Zhao, Moju; Kawasaki, Koji; Anzai, Tomoki; Chen, Xiangyu; Noda, Shintaro; Shi, Fan; Okada, Kei; Inaba, Masayuki
A multirotor with two-dimensional multilinks is proposed to perform aerial transformation and aerial manipulation. First, a modular link structure that comprises a multirotor with a reliable internal communication system was initially developed. Second, a flight control method was further introduced on the basis of linear–quadratic–integral optimal control for aerial transformation. A relaxed hovering solution that neglects the yaw motion stability is proposed to enable stable flight under a certain singular form. Third, the transformable robot was employed as an entire gripper with regards to grasping to perform the whole-body aerial manipulation. A grasp-form searching method was developed to optimize hovering thrust force and joint torque under force-closure grasp, and was followed by an aerial approach and grasp-motion strategy to fulfill the resulting desired grasp form. Finally, experimental results demonstrate the stable aerial transformation as well as the feasibility of the whole-body aerial manipulation system to grasp and carry different types of objects.